Obstructe d Labour: A Life Threatening Complication - Khatun, Jamila; Khanom, Khudeja (Medicine Today, 2017)
Obstructed labour is an important cause of maternal death in developing countries. Obstructed labour also causes significant maternal morbidity mainly due to infection and hemorrhage and foetal death from asphyxia is also common. Objectives are to reduce maternal and newborn complications by early detection and rapid interventions and to reduce maternal and perinatal morbidity and mortality. This Hospital-based prospective cross-sectional study was conducted from June 2013 to June 2014 in Sylhet, MAG Osmani Medical College Hospital. 100 obstructed labour cases were selected those who were admitted in Inpatient department of Obstetrics and Gynaecology, SOMCH. 100 obstructed labour cases were recorded. The majority (80%) were residents of rural areas in which transportation were difficult, the occupation of the women were housewives mostly (90%) and remaining (10%) were tea-garden worker.75% of the obstructed labour cases did not have any ante-natal follow-up. Most of the cases (70%) were visited Osmani Medical College Hospital by their attendant. 70% Visited at 12-24 hours of labour, (80%) came from a distance of 10-50 kilometers. Cepholo-pelvic disproportion was the major cause of obstructed labour (78%) and cesarean section was the main way of delivery (95%). PPH (4%), puerperal sepsis (4%), rupture uterus (2%), VVF (2%), rupture uterus with shock (1%), were the main complications and maternal death (1%). Obstructed labour was the major causes of poor perinatal outcome and perinatal death (7%). This study revealed high incidence of maternal morbidity and perinatal morbidity and mortality. Medicine Today 2017 Vol.29(1): 12-14